SAXS imaging reveals optimized osseointegration properties of bioengineered oriented 3D-PLGA/aCaP scaffolds in a critical size bone defect model. (March 2023) - Casanova, Elisa A.; Rodriguez-Palomo, Adrian; Stähli, Lisa; Arnke, Kevin; Gröninger, Olivier; Generali, Melanie; Neldner, Yvonne; Tiziani, Simon; Dominguez, Ana Perez; Guizar-Sicairos, Manuel; Gao, Zirui; Appel, Christian; et al.
Abstract: Healing large bone defects remains challenging in orthopedic surgery and is often associated with poor outcomes and complications. A major issue with bioengineered constructs is achieving a continuous interface between host bone and graft to enhance biological processes and mechanical stability. In this study, we have developed a new bioengineering strategy to produce oriented biocompatible 3D PLGA/aCaP nanocomposites with enhanced osseointegration. Decellularized scaffolds -containing only extracellular matrix- or scaffolds seeded with adipose-derived mesenchymal stromal cells were tested in a mouse model for critical size bone defects. In parallel to micro-CT analysis, SAXS tensor tomography and 2D scanning SAXS were employed to determine the 3D arrangement and nanostructure within the critical-sized bone. Both newly developed scaffold types, seeded with cells or decellularized, showed high osseointegration, higher bone quality, increased alignment of collagen fibers and optimal alignment and size of hydroxyapatite minerals.